Efektifitas Metode Edukasi Kesehatan Lingkungan pada Keluarga Beresiko Stunting - Rosita, Yeni; Widya Ningsih, Gusti; Utama, Susan Rendra (Universitas Malahayati Bandar Lampung, 2024)
Background: The problem of stunting is one of the problems faced in the world, especially in poor and developing countries. Stunting is a problem because it is associated with an increased risk of morbidity and death, sub-optimal brain development so that motor development is hampered and mental growth is delayed. Lampung Province is one of the provinces that contributes the highest stunting data. Based on data from the Lampung Provincial Health Service in 2021, the results of the 2019 Indonesian Nutrition Status Study (SSGI) survey, the stunting rate in Lampung was 26.26 percent and 19.4 percent came from Bandar Lampung City. According to screening data for potential risks of stunting, one of the sub-districts contributing to stunting is Kemiling Sub-district. The number of heads of families in Kemiling District is 17,506 families. The target families according to the screening for potential risks of stunting were 11,428 families and 8,672 families of them were in the category of families at risk of stunting. Sumber Agung Village is one of the villages in Kemiling District, Bandar Lampung City. This subdistrict with 1,020 families has 305 people at risk of stunting and 246 families do not have an adequate main source of clean water. Counseling is an activity in an effort to provide understanding to parents so they know the causes of stunting problems. Counseling aims to increase knowledge of parents so that they are able to take action to prevent stunting as early as possible.Purpose: To find out the effectiveness of environmental health education methods for families at risk of stunting in Sumber Agung Village, Kemiling District, Bandar Lampung City in 2024.Methods: is Quasi Experimental with a research design using Pretest-Posttest Design. This research will carry out observations twice, namely before (Pretest) and after (Posttest), this research was conducted in Sumber Agung Village with a sample size of 246 families of stunted toddlers using purposive sampling techniques. The collected data will be analyzed using the SPSS 22 statistical program. Bivariable data analysis was carried out using the paired t test with a significance level of p<0.05.Results: The results of research on providing educational methods door to door and in groups show that the increase in knowledge and attitudes increases with the education method through groups with an increase in knowledge of 75.2% and attitudes of 81.8%. Comparison of the Effectiveness of Environmental Health Education Methods in Families at Risk of Stunting shows that the group method is the most effective with a pretest average of 25.5 and an increase of 37.1 with a p-value of 0.000 so it can be concluded that it is very related and effective.Conclusion: Apart from methods, effectiveness also depends on other aspects such as the involvement of facilitators, relevant educational content, as well as environmental and government support in efforts to prevent stunting.Keywords: method; education; effective